LO18: How big is emergency access block in Canadian hospitals?. (15th May 2017) - Innes, G.; Sivilotti, M.; Ovens, H.J.; Chochinov, A.; McLelland, K.; Sing, C. Kim; MacKinnon, D.J.; Chopra, A.; Dukelow, A.; Horak, S.; Barclay, N.; Kalla, D.; et al.
Abstract : Introduction: Emergency department (ED) access block is the #1 safety concern in Canadian EDs. Its main cause is hospital access block, manifested by prolonged boarding of inpatients in EDs. Hospital administrators often believe this problem is too big to be solved and would require large increases in hospital capacity. Our objective was to quantify ED access gap by estimating the cumulative hours that CTAS 1-3 patients are blocked in waiting areas. This value, expressed as a proportion of inpatient care capacity, is an estimate of the bed hours a hospital would have to find in order to resolve ED access.Methods: A convenience sample of urban Canadian ED directors were asked to provide data summarizing their CTAS 1-3 inflow, the proportion triaged to nursed stretchers vs. RAZ or Intake areas, and time to care space. Total ED access gap was calculated by multiplying the number of CTAS 1-3 patients by their average delay to care space. Time to stretcher was captured electronically at participating sites, but time to RAZ or intake spaces was often not. In such cases, respondents provided time from triage to first RN or MD assessment in these areas. The primary outcome was total annual ED access block hours for emergent-urgent patients, expressed as a proportion of funded inpatient bed hours.Results: Directors of 40 EDs were queried. Six sites did not gather the data elements required. Of 34 remaining, 29 (85.3%) provided data, including 15 tertiary (T), 10 community (C) and 2 pediatric (P) sites in 12 cities. Mean census for the 3 ED types was 72, 308 (T), 58, 849 C) and 61, 050 (P) visits per year. CTAS 1-3 patients accounted for 73.4% (T), 67.7% (C) and 66.2% (P) of visits in the 3 groups, and 34% (T), 46% (C) and 44% (P) of these patients were treated in RAZ or intake areas rather than staffed ED stretchers. Mean time to stretcher/RAZ care was 50/71 min (T), 46/62 min (C), and 37/59 min (P). Average ED access gap was 47, 564 hrs (T), 37, 222 hrs (C) and 35, 407 hrs (P), while average inpatient bed capacity was 599 beds (5, 243, 486 hrs), 291 beds (2, 545, 875 hrs) and 150 beds (1, 314, 000 hrs) respectively. ED access gap as a proportion of inpatient care capacity was 0.93% for tertiary, 1.46% for community and 2.69% for pediatric centres.Conclusion: ED access gap is very large in Canadian EDs, but small compared to hospital operating capacity. Hospital capacity or efficiency improvements in the range of 1-3% could profoundly mitigate ED access block.